Prevention of migraine in children and adolescents: results of an open-label study with special extract of Petasites hybridus root - Kaup, Alexandre (Headache Medicine, 2025)
IntroductionMigraine is a genetic disease that has a major impact on life. Its prevalence is estimated to be 7.7% up to the age of 20. Preventive treatment of migraine in childhood and adolescence remains a challenge, due to the few studies conducted for this population and the presence of side effects in the use of the medications used. MethodIn this article, we evaluated the prospective open study conducted by Pothmann and Danesch using Petasites hybridus extract as a preventive treatment for migraine in children (6-9 years) and adolescents (10-17 years). ResultsThis open study showed that at the end of the 4 months of treatment with Petasites hydbridus the reduction in migraine attacks in the total sample was 63.2%, 67% for children aged 6 to 9 years and 61.9% for adolescents aged 10 to 17 years. The overall response rate was 77.2%, with 85.7% for the 6- to 9-year-old group and 74.1% for the 10- to 17-year-old group. There was also a reduction in the mean duration of attacks in 62.7% of patients, from approximately 10 hours to 7 hours. No significant side effects were observed.ConclusionPetasites hybridus proved to be a safe and effective option for the preventive treatment of migraine in children and adolescents.